TANTANGAN PENDIDIKAN KRISTEN MENGHADAPI PENGARUH SEKULARISME [THE CHALLENGE OF CHRISTIAN EDUCATION FACING THE INFLUENCE OF SECULARISM IN SCHOOLS] - Tarigan, Musa Sinar (Polyglot, 2025)
Secularism has been influencing the way of thinking and acting in all areas of human life, including religion and education. Secularism’s aims to enable different human beings to do their functions as members of community, free from conflicts caused by religious (Christian) values. This goal can be achieved by removing religious beliefs from the public sphere to the private sphere or denying faith involvement in social life. Secularism rejects the absoluteness of God and so this view is contrary with God's revelation in the Bible. This secularism has impacts on Christian education, such as, the God’s Truth is not foundation of Christian education, students are not educated to know God, education prepares students to work according to the purpose of secularism. The purpose of this article is to explain that the principles of Christian faith based on the Bible relevant in the lives of Christians and the foundation of education to overcome the influence of secularism. This article uses descriptive qualitative approach by analysing the influence of secularism in education through various relevant literature sources. This data is analysed based on biblical principles to find how the role of Christian faith in the Bible faces the influence of secularism in education. The writing of this article explains that the principles of Christian faith relevant as the foundation of Christian education to lead students to know God and grow more like Christ, that God has authority over His creation, so that human life depends on God.  Abstrak bahasa Indonesia  Sekularisme telah mempengaruhi sistem berpikir dan bertindak seluruh bidang kehidupan manusia, termasuk bidang agama maupun pendidikan. Pemikiran sekularisme bertujuan agar manusia yang berbeda-beda dapat menjalankan fungsinya sebagai anggota masyarakat, bebas dari konflik yang disebabkan oleh nilai agama (kristen). Tujuan tersebut dapat dicapai dengan menyingkirkan keyakinan agama dari wilayah publik kepada wilayah pribadi, atau menolak keterlibatan iman dalam kehidupan bermasyarakat. Sekularisme menolak kemutlakan Allah sehingga pandangan ini bertentangan dengan wahyu Allah dalam Alkitab. Seklarisme ini memberikan dampak dalam pendidikan Kristen, yaitu, Alkitab tidak menjadi dasar dalam pendidikan Kristen, para siswa tidak dididik, dituntun untuk mengenal dan bertumbuh mengenal Allah, pendidikan mempersiapkan para siswa untuk bekerja sesuai tujuan jaman sekularisme. Tujuan penulisan artikel ini untuk menjelaskan bahwa prinsip iman Kristen berdasarkan Alkitab tetap relevan dalam hidup orang Kristen dan dasar pendidikan untuk mengatasi pengaruh sekularisme ini.  Penulisan artikel menggunakan pendekatan kualitatif deskriptif dengan menganalisis pengaaruh sekularisme dalam pendidikan melalui dari berbagai sumber literatur yang relevan. Data tersebut kemudian dianalisis berdasasarkan prinsip Alkitab untuk menemukan bagaimana peran iman Kristen dalam Alkitab menghadapi pengaruh sekularisme pendidikan. Penulisan artikel ini menunjukkan bahwa prinsip iman Kristen tetap relevan menjadi dasar dalam pendidikan Kristen untuk menuntun siswa mengenal Allah dan bertumbuh semakin serupa Kristus, Allah memiliki otoritas atas ciptaan-Nya, hidup manusia bergantung kepada Allah.